Inhibition of exocytosis or endocytosis blocks activity-dependent redistribution of synapsin - Orenbuch, Ayelet; Vasileva, Mariya; Kuner, Thomas (Journal of neurochemistry, 2012)
The synaptic vesicle cycle encompasses the pre-synaptic events that drive neurotransmission. Influx of calcium leads to the fusion of synaptic vesicles with the plasma membrane and the release of neurotransmitter, closely followed by endocytosis. Vacated release sites are repopulated with vesicles which are then primed for release. When activity is intense, reserve vesicles may be mobilized to counteract an eventual decline in transmission. Recently, interplay between endocytosis and repopulation of the readily releasable pool of vesicles has been identified. In this study, we show that exo-endocytosis is necessary to enable detachment of synapsin from reserve pool vesicles during synaptic activity. We report that blockage of exocytosis in cultured mouse hippocampal neurons, either by tetanus toxin or by the deletion of munc13, inhibits the activity-dependent redistribution of synapsin from the pre-synaptic terminal into the axon. Likewise, perturbation of endocytosis with dynasore or by a dynamin dominant-negative mutant fully prevents synapsin redistribution. Such inhibition of synapsin redistribution occurred despite the efficient phosphorylation of synapsin at its protein kinase A/CaMKI site, indicating that disengagement of synapsin from the vesicles requires exocytosis and endocytosis in addition to phosphorylation. Our results therefore reveal hitherto unidentified feedback within the synaptic vesicle cycle involving the synapsin-managed reserve pool.